Using social media to enhance student engagement and quality - Lottering, R.A. (South African Journal of Higher Education, 2020)
The educational benefits, which accrue from the enhancement in student engagement, are well documented in the literature. Some of the benefits identified include increased student interest in course content, enhanced academic performance and enhanced student critical thinking skills. This study demonstrates a significant advantage in using social media platforms in student engagement with the course material and lecturers offering the material. Typically, student engagement has been and mainly is achieved as on-campus contact mode or contact at sites of delivery and even online, using platforms created and managed by universities such as Blackboard. In this study, a comparative review of the academic performance of two groups of students enrolled for a similar subject offered at a University of Technology is performed to analyze the effects of using social media as a method to engage students on performance outside the normal communication time. The assumption is that this method of student engagement would enrich the student experience and alter how course content is articulated, presented and absorbed, in essence allowing the student to feel enabled and included in the engagement paradigm. Feedback provided in the engagement with peers and the lecturer leads to clarity and improvement in the quality of the course overall.